(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2014)
Mucopolysaccharidosis (MPS) is a type of storage disorders which can affect the skin, liver, spleen, eye, brain and bone. Some variant present in early infancy and others present in late childhood. Clinical, biochemical and radiological evaluations are needed for a conclusive diagnosis. We present a case of MPS with various radiological findings of spines and skull which helped in the diagnosis of the condition in a resource poor setting like that of us. JCMCTA 2013 ; 24 (2): 51-52